Pemahaman Siswa SMA/SMK Kota Pasuruan Terhadap Hak dan Kewajiban Tenaga Kerja berdasarkan UU Ketenagakerjaan di Indonesia - M. Mascun Andianto; Arum Masyitoh; Ajijah Ajijah; Firza Agung Prakoso (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Employment law education plays an important role in equipping the younger generation, especially high school and vocational high school students, with an understanding of the rights and obligations as prospective workers. This study aims to analyze the relationship between students' understanding of employment law and employment rights and obligations. Using a quantitative approach, data were collected through questionnaires from grade XI students at SMAN 3 Pasuruan, SMKN 1 Pasuruan, and SMK PGRI 2 Pasuruan. The validity results showed that all questionnaire items were valid (100%), while the reliability of the variables showed a Cronbach Alpha value of 0.606 for student understanding and 0.778 for labor rights and obligations. The simple linear regression model showed a significant positive relationship with the regression equation Y = −0.833 + 0.997XY = -0.833 + 0.997X and an R Square value of 0.600, which means that 60% of the variation is explained by the model. This study confirms that employment law education has a real impact on students' legal awareness, supporting their preparation to face the world of work with a better understanding